(untitled) (International Journal of Engineering and Computer Science, 2014)
Watermarking schemes has been proposed as a protection of data or in other words preventing illegal copying of data, but still this security is yet to be well defined. The approach of watermarking is sometimes considered too theoretical. Hence, a whole new casting of watermark security is proposed, called the effective key length. Through this approach it would be a nightmare for any hacker who tries to find access to the original data and also digital watermarking technique is used as the embedding process for data hiding, apart from using security keys, because finding the key should not be the best mode in breaking the system therefore multiple level of security is proposed in this paper. The analysis paves way to the spread spectrum scheme to initiate the theoretical and practical application of the effective key length. For data hiding, ISS (Improved Spread Spectrum) offers a better security and robustness and it is adopted to implement digital invisible ink method.